"Put Your Ear Close to the Whispering Branch..." Deep Listening in the English Classroom - Jessica Jones (Journal of the Assembly for Expanded Perspectives on Learning, 2015)
Taking her cue from Guy Murchie’s Song of the Sky, the author discovers a method for reaching at-risk children, whose ventures into poetry engage them deeply in the natural world and make them part of it.